Identificación de consorcios microbianos fotosintéticos a partir de suelos hortícolas de la provincia de Loja - Jiménez Gordillo, Stefany Tatiana (2024)
Currently, environmental pollution derived from the excessive use of chemicals has become a global problem. In the province of Loja, it has become known that the use of different agrochemicals is commonly used in cultural crops, such as corn, tomatoes, vegetables, among others. To protect soil microorganisms from the harmful effects of agrochemicals, it is necessary to minimize their use, allowing their recovery and their action in different activities that they carry out in the soil, accelerating the biodegradation process. Microbial consortia are of ecological and biotechnological importance because they contribute to biogeochemical cycles and produce compounds of high added value. For this reason, the objective of this research was to identify photosynthetic microbial consortia from horticultural soils in the province of Loja, intended for the cultivation of tomato, pepper and lettuce. Nine consortia were identified and characterized, which were identified 10 in the BG11 culture medium, where there was greater growth; in addition, a strain collection was developed for future studies related to the production of products based on them. . The microbial consortia demonstrate the application capabilities in agronomy, and allow us to glimpse its possible biotechnological application as a bio-fertilizer. The samples evaluated gave us a result greater than 70% regarding the presence of the micro-algae Chlorella, which is a soil-forming agent, thanks to the production of polysaccharides and mucilaginous substances that provide minerals and help with structuring.